MENGGUNAKAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN KETERAMPILAN SISWA MENULIS KARANGAN DESKRIPSI MATA PELAJARAN BAHASA INDONESIA SISWA SEKOLAH DASAR - Kori Sundari; Rima Rikmasari; Mayang (Jurnal PAJAR (Pendidikan dan Pengajaran), 2022)
This article examines the obstacles that occur to students’ writing essay descriptions in which the type of students’ writing is almost the same, does not use spaces, the lettering is still not appropriate with PUEBI, punctuation marks are not quite right, and the students are still difficult to write the appropriate initial word and determine the flow of writing in sequence. Based on the previous research, the picture and picture model was a solution that could be used. The research purpose was to find out the description of the use of picture and picture models in writing descriptive essays. The research method used was a Systematic Literature Review. The research was conducted by collecting data in the form of journals regarding the application of picture and picture models to improve the students’ writing skills of descriptive essays on Indonesian learning subjects in elementary school. The research used 14 journals with criteria for the last 10 years of journal publication in 2012–2013 through a picture and picture model with independent variables used to write descriptive essays on Indonesian learning subjects for elementary school students. The game that could be used in the application of the picture and picture model was "who is fast he can", this game made students easier to understand what was intended by the teachers when teaching the learning material and students are quick to grasp the presented material because it was accompanied by the pictures.